2015
DOI: 10.1371/journal.pone.0134105
|View full text |Cite
|
Sign up to set email alerts
|

Life-History Traits of the Model Organism Pristionchus pacificus Recorded Using the Hanging Drop Method: Comparison with Caenorhabditis elegans

Abstract: The nematode Pristionchus pacificus is of growing interest as a model organism in evolutionary biology. However, despite multiple studies of its genetics, developmental cues, and ecology, the basic life-history traits (LHTs) of P. pacificus remain unknown. In this study, we used the hanging drop method to follow P. pacificus at the individual level and thereby quantify its LHTs. This approach allowed direct comparisons with the LHTs of Caenorhabditis elegans recently determined using this method. When provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…8). 177 Importantly, this is still within the egg-laying period 32 , potentially contributing to increased 178 fitness. Nevertheless, these assumptions are subject to several difficult-to-measure factors that 179 could both positively and negatively affect K, such as the consumption rate of other nematode 180 .…”
mentioning
confidence: 99%
“…8). 177 Importantly, this is still within the egg-laying period 32 , potentially contributing to increased 178 fitness. Nevertheless, these assumptions are subject to several difficult-to-measure factors that 179 could both positively and negatively affect K, such as the consumption rate of other nematode 180 .…”
mentioning
confidence: 99%
“…The pre-hatch development timeline was initially observed using a hanging drop method with modifications [24]. Single eggs were added to 6 μl of either water or a hatching stimulant in a concave well microscope slide and covered with a coverslip.…”
Section: Methodsmentioning
confidence: 99%
“…The first of these traits, lifetime fecundity, was chosen based on its use as a standard life‐history measure (Gilarte et al. ) and its demonstrated ability to detect fitness differences on alternative diets in P. pacificus (Rae et al. ; Serobyan et al.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we recorded brood sizes and growth rates for the wild-type strain and all single, double, and triple mutants. The first of these traits, lifetime fecundity, was chosen based on its use as a standard life-history measure (Gilarte et al 2015) and its demonstrated ability to detect fitness differences on alternative diets in P. pacificus (Rae et al 2008;Serobyan et al 2014). We measured the second trait, growth rate, because of the previous detection of differences in rates between the two mouth-morphs on a similar diet, albeit with a finer time-course than what we employ here (Serobyan et al 2013).…”
Section: Phenotypic Assaysmentioning
confidence: 99%